Advancing STEM Education through Inquiry, Equity, and Cultural Relevance: - Faizal Akhmad; Udan Kusmawan (International Journal of Research in STEM Education)
This editorial introduces the first issue of International Journal of Research in STEM Education (IJRSE) for 2025, presenting a diverse collection of nine articles, including empirical studies, conceptual analyses, and case-based research. The contributions span across seven countries—Korea, Namibia, the Philippines, Indonesia, Nigeria, Mexico, and Taiwan—representing four continents and fifteen institutions. This issue exemplifies a shared global commitment to address key challenges in STEM education through culturally grounded innovation, interdisciplinary pedagogy, and inclusive policy perspectives. Themes emerging from the articles include inquiry-based and project-based strategies, indigenous knowledge integration, differentiated instruction, equity in science learning, and STEM professional development. Together, these studies chart critical pathways for advancing quality, relevance, and access in STEM education, providing insights that are both context-specific and globally resonant.